Physicochemical Characteristics And Essential Minerals Of Zink (Zn) Trash Fish Nugget Products - Warsidah (Jurnal Ilmiah PLATAX, 2023)
Fish nuggets are processed frozen foods, both made from seawater fish and freshwater fish, contain high nutritional value, and are favored by children and adolescents as snacks and as side dishes. This study aimed to determine the physicochemical characteristics of trash fish nuggets added with Eucheuma cottonii seaweed. The physicochemical characteristics include pH, proximate levels such as protein, fat, and carbohydrates, water content and ash content, and the essential mineral content of zinc (Zn). Trash fish nuggets with the addition of wheat flour alone have characteristics, including pH of 6.8-7.1, water content of 40.5%, ash content of 1.04%, protein content of 40.3%, fat content of 7 0.07% and carbohydrate content of 10.12%, zinc content of 2.55 g/g nugget weight, while trash fish nuggets with the addition of a mixture of wheat flour and E. cottonii had a pH of 6.8-7.1, water content of 42.5%, ash content of 1.22%, protein content of 42.9%, fat content of 5.97% and carbohydrate content of 4.11% and zinc content of 4.56 g/g nugget weight. Based on the organoleptic examination, trash fish and E. cottonii nuggets were chewy with a delicious and savory taste. Keywords: characteristics, phytochemistry, E. cottonii, nuggets, trash fish Abstrak Nugget ikan merupakan salah satu olahan pangan frozen food, baik berbahan ikan air laut maupun ikan air tawar, mengandung nilai gizi tinggi dan digemari oleh anak-anak dan remaja sebagai cemilan maupun sebagai lauk. Penelitian ini bertujuan untuk menentukan karakteristik fisikokimia dari nugget ikan rucah yang ditambahkan dengan rumput laut Eucheuma cottonii. Karakteristik fisikakimia meliputi pH, kadar proksimat seperti protein, lemak dan karbohidrat, kadar air dan kadar abu serta kandungan mineral essensial seng (Zn). Nugget ikan rucah dengan penambahan tepung gandum saja memiliki karakteristik antara lain pH sebesar 6,8-7,1, kandungan air sebesar 40,5 %, kadar abu sebesar 1,04 %, kadar protein sebesar 40,3 %, kadar lemak sebesar 7,07 % dan kadar karbohidrat sebesar 10,12 %, kandungan seng sebesar 2,55 μg/g bobot nugget, sedangkan nugget ikan rucah dengan penambahan campuran tepung gandum dan E. cottonii memiliki pH sebesar 6,8-7,1, kandungan air sebesar 42,5 %, kadar abu sebesar 1,22 %, kadar protein sebesar 42,9 %, kadar lemak sebesar 5,97 % dan kadar karbohidrat sebesar 4,11 % serta kandungan seng sebesar 4,56 μg/g bobot nugget. Berdasarkan pemeriksaan organoleptis menunjukkan produk nugget ikan rucah dan E. cottoni lebih kenyal dengan rasa yang lezat dan gurih. Kata kunci: karakteristik, fisikokimia, E. cottonii, nugget, ikan racuh